Inserção do Design em Micro e Pequenas Empresas: o caso de duas indústrias moveleiras no Estado do Rio Grande do Norte - Santos, Suely Xavier dos (2007)
This work aims to promote design aspects into furniture Small and Medium Enterprises (SME s) at Rio Grande do Norte State. The final outcome will be an increasing on their competitiveness as well as consider design as key strategic aspect for their business. As a consequence, the results are based on two SME companies from the furniture sector located at Natal/RN. The study is based on a literature research followed by a management diagnosis for each company. The diagnosis was base don interviews with the entrepreneurs and their employees as well as meetings, participant observations and document analysis. Based on this analysis, specific aspects were implement in order to boost the production line as well as the product development process (PDP) and the development of a prototype. The results have indicated some limitation of these companies regarding their low technological on their production line, poor management and work skills as well as low perception of design as a competitive tool. Regardless these results, it was observed that design has brought an important contribution for cultural changes within companies as well as for the development of better quality and competitive products